PERILAKU PROSOSIAL REMAJA : BAGAIMANA PERAN KELEKATAN ORANGTUA? - Naufal Ridho Kushernanda; Niken Titi Pratitis; Isrida Yul Arifiana (Fakultas Psikologi Universitas Tarumanagara, 2023)
This research was conducted to determine the correlation between parental attachment and prosocial behavior in adolescents. This research was conducted on 118 adolescents in the Gubeng District, Surabaya City. Data collection techniques using a research scale that is shared online. There are two scales used in this study, namely the attachment scale and the prosocial behavior scale. The data from this study were calculated with the help of SPSS version 25.0 for windows using the Spearman's rho correlation technique. The results of this study indicate a positive and significant relationship so that it can be assumed that the higher the parental attachment, the higher the prosocial behavior possessed by adolescents.